Philippine Journal of Development. (Makati Philippine Institute for Development Studies, 2001)
Contains articles on a wide range of issues that includ not only studies on the economy but also on other aspects of development. Includes technical and policy oriented studies related to business, political dynamics, public administration, foreign relations and the like which have a bearing on Philippine development.
Previously issued as NEDA Journal of Developement and later as Journal of Philippine Development.
Keywords: Economic development -- Philippines